Tests and Proofs 8th International Conference, TAP 2014, Held as Part of STAF 2014, York, UK, July 24-25, 2014, Proceedings - Seidl, Martina; Tillmann, Nikolai (Programming and Software Engineering, 2014)
This book constitutes the refereed proceedings of the 8th International Conference on Tests and Proofs, TAP 2014, held in York, UK, in July 2014, as part of the STAF 2014 Federated Conferences. The 10 revised full papers and 4 short papers presented together with two tutorial descriptions were carefully reviewed and selected from 27 submissions. The papers cover topics in the following four research areas: test generation, bridging semantic gaps, integrated development processes and bounded verification.